i-Know: revolutionizing knowledge management with interactive quizzes - Zulkifli, Zahidah; Abdul Halim, Muhammad Darwish Irfan; Shaffei Mohammad, Arief Iskandar; AlSaiari, Nisrin (IEEE, 2024)
This project focuses on the development of a website system designed to facilitate knowledge acquisition for students enrolled in the Kulliyyah of Information Communication and Technology (KICT) at the International Islamic University Malaysia (IIUM). The aim is to alleviate the information overload experienced by new intake students during the Taaruf week (orientation week). Despite its establishment in 2010, KICT faces a persistent challenge where new students remain unaware of crucial system details, including rules, regulations, and academic matters. To address this issue, the project endeavors to provide a comprehensive platform enabling new students to access pertinent information and knowledge about KICT. An analysis of seven similar existing systems has been conducted, highlighting their main functions, advantages, and disadvantages. The System Development Life Cycle methodology has been selected for its practicality in guiding the project through the phases of FYP1 and FYP2. Data collection involved surveying 30 KICT students to identify challenges faced by new students in obtaining the necessary information. Results underscore the urgent need for a technically guided application to enhance student understanding of KICT. The logical design of the app encompasses a Use Case Diagram, Use Case Narrative, Activity Diagram, Interface Flow, Low-Fidelity Design, and Interface Flow. The "i-know" system has been developed using PHP, HTML, CSS, and Javascript, with connectivity to MySQL through phpMyAdmin for user authentication. The User Acceptance Test (UAT) was conducted during implementation, following beta testing. The paper concludes with insights into the system's effectiveness and its potential to address the identified challenges faced by new KICT students.